Propensity Scores: A Practical Introduction Using R - Antonio Olmos; Priyalatha Govindasamy (The Evaluation Center at Western Michigan University, 2015)
Background: This paper provides an introduction to propensity scores for evaluation practitioners.     Purpose: The purpose of this paper is to provide the reader with a conceptual and practical introduction to propensity scores, matching using propensity scores, and its implementation using statistical R program/software.   Setting: Not applicable   Intervention: Not applicable   Research Design: Not applicable       Data Collection and Analysis: Not applicable   Findings: In this demonstration paper, we describe the context in which propensity scores are used, including the conditions under which the use of propensity scores is recommended, as well as the basic assumptions needed for a correct implementation of the technique. Next, we describe some of the more common techniques used to conduct propensity score matching. We conclude with a description of the recommended steps associated with the implementation of propensity score matching using several packages developed in R, including syntax and brief interpretations of the output associated with every step.   Keywords: propensity score analysis; propensity score matching; R.